Numerical Simulation of the Blast Resistance of SPUA Retrofitted CMU Masonry Walls - Yi Zhang; Jiahui Hu; Wenda Zhao; Feng Hu; Xiao Yu (Buildings, 2023)
Through numerical simulation, the blast-resistant performance of spray polyurea elastomer (SPUA) retrofitted concrete masonry unit (CMU) masonry infill walls under far-range blast loading was studied. From an engineering perspective, the effects of boundary conditions and thickness of a SPUA layer on enhancing the blast resistance of masonry infill walls are discussed, and the blast resistance of SPUA-retrofitted and grouted CMU masonry infill walls are compared. It is concluded that the boundary constraint conditions and the anchorage length of SPUA layer have limited improvement on the blast-resistant performance of the wall; the thickness of SPUA layer can significantly improve the blast-resistant performance of the wall as the blast loading increases. In addition, SPUA retrofitting shows relatively better performance to reinforce masonry infill walls.